Suppression of runaway electrons by mode locking during disruptions on J-TEXT. (22nd June 2018) - Chen, Z.Y.; Lin, Z.F.; Huang, D.W.; Tong, R.H.; Hu, Q.M.; Wei, Y.N.; Yan, W.; Dai, A.J.; Zhang, X.Q.; Rao, B.; Yang, Z.J.; Gao, L.; et al.
Abstract: The generation of runaway electrons during disruptions poses a serious threat for the operation of ITER. The efficiency of the injection of large amounts of impurities by massive gas injection or shattered pellet injection to achieve runaway suppression might be compromised due to low gas mixture efficiency and the high Rosenbluth density for runaway suppression. The transport of runaway electrons is dominated by magnetic perturbations. The magnetic perturbations have the advantage of expelling the runaway seeds before they reach high energy. Robust runaway suppression has been reached on J-TEXT with mode locking by the application of m / n = 2/1 resonant magnetic perturbations before the thermal quench. The mode locking implemented large magnetic islands inside the plasma which acted as an explosive bomb during disruptions and led to stronger stochasticity in the whole plasma cross section. The NIMROD simulation indicates that this strong stochasticity expels the runaway seeds and results in runaway free disruptions on J-TEXT. This might provide an alternative runaway suppression technique during disruptions for large-scale tokamaks.